Two Classes of Cytoplasmic Viral RNA Synthesized Early in Productive Infection with Adenovirus 2 - Craig, Elizabeth A. (1974)
The RNA sequences and RNA size classes transcribed early in productive infection with adenovirus 2 were analyzed by RNA-DNA hybridization. Two independent procedures demonstrated that early cytoplasmic viral RNA is composed of two sequence classes, class I which is absent or present in greatly reduced quantities at 18 h, and class II which persists throughout the infection. When the sequences in early viral RNA were analyzed by hybridization-inhibition studies, the hybridization of early [(3)H]RNA was inhibited only 50% by RNA from cultures harvested late (18 h) in infection. Liquid hybridizations with radioactive viral DNA confirmed that early RNA includes two classes. Duplex formation of RNA with (32)P-labeled viral DNA was assayed by hydroxylapatite chromatography and resistance to S(1) nuclease digestion. Both methods showed that the cytoplasmic RNA present early in infection annealed 12 to 15% of the viral DNA; late cytoplasmic RNA hybridized 21 to 25% of the DNA. Mixtures of early plus late cytoplasmic RNAs hybridized 30 to 34% of the viral DNA, demonstrating the reduced concentration of early class I RNA in the late RNA preparations. Experiments were performed to correlate class I and class II early RNA with size-fractionated cytoplasmic RNA synthesized early in infection. Fractionation of RNA by gel electrophoresis or sucrose gradient centrifugation confirmed three major size classes, 12 to 15S, 19 to 20S, and 26S. Total cytoplasmic RNA and RNA selected on the basis of poly(A) content contained the same size classes of viral RNA. In standard electrophoresis conditions, the 19 to 20S viral RNA could be resolved into two size classes, and the distribution of 12 to 15S RNA also indicated the presence of more than one size component. Hybridization-inhibition studies under nonsaturating conditions were performed with 26S, 19 to 20S, and 12 to 15S viral RNAs fractionated by gel electrophoresis. Late RNA inhibited the hybridization of 26S RNA only 20%, 19 to 20S RNA was inhibited 45%, and 12 to 15S RNA was inhibited 50%. When 18 to 19S and 12 to 15S viral RNAs purified by sucrose gradient centrifugation were similarly analyzed, late RNA inhibited hybridization of 18 to 19S RNA 50%, and the annealing of 12 to 15S RNA was inhibited 70%.